Unveiling Emotional Experiences: Factors Affecting Anxiety in Undergraduate English Language Learning - Neneng Islamiah; Yudha Aprizani; Tenny Murtiningsih (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2023)
The objective of this research was to delve into the emotional experiences of undergraduate English students, specifically focusing on their feelings of anxiety and nervousness. Furthermore, the study aimed to identify the various factors that contribute to these feelings among undergraduate English students while learning to speak English. This research was qualitative research conducted at a private university in Banjarmasin with four participants. In collecting the research data, researcher semi-structured interview techniques and the data were analysed using thematic inductive analysis. From the results of the research conducted, it was found that there were three undergraduate students who experienced dominant negative emotions during learning to speak English, while another student considered that negative emotions did not dominate him too much. There were two main factors that cause anxiety and nervousness, namely external factors (such as lack of confidence and the environment) and internal factors (such as lack of mastery of grammar and vocabulary)